Institutional Reform and Depositors' Portfolio Choice: Evidence from Censored Quantile Regressions - Marc-André Luik; Michael Berlemann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
The determinants of portfolio choice have been studied extensively in the field of household finance. In this paper we study the determinants of the decision to hold risky assets based on a novel dataset of German bank data. Our primary focus is the question whether East Germans di er in their portfolio decisions from West Germans. While we find only slight di erences in the decision to invest in risky assets at the extensive margin, the di erences at the intensive margin turn out to be much larger and non-linear. We attribute this finding to the di erent institutional environments East and West Germans experienced throughout the period of German division.
Keywords: G21; O16; D14; 330